Paradise, death, and doomsday in Anglo-Saxon literature - Kabir, Ananya Jahanara, 1970- (Cambridge studies in Anglo-Saxon England, 2001)
"How did the Anglo-Saxons conceptualise the interim between death and Doomsday? In Paradise; Death and Doomsday in Anglo-Saxon Literature, Ananya Jahanara Kabir presents the first investigation into the Anglo-Saxon belief in the 'interim paradise'; paradise as a temporary abode for good souls following death and pending the final decisions of Doomsday. She locates the origins of this distinctive sense of paradise within early Christian polemics, establishes its Anglo-Saxon developments as a site of contestation and compromise, and argues for its post-Conquest transformation into the doctrine of purgatory. In ranging across Old English prose and poetry as well as Latin apocrypha, exegesis, liturgy, prayers and visions of the otherworld, and combining literary criticism with recent scholarship in early medieval history, early Christian theology and history of ideas, this book is essential reading for scholars of Anglo-Saxon England, historians of Christianity, and all those interested in the impact of the Anglo-Saxon period on the later Middle Ages."--Jacket